PENGARUH PENGETAHUAN INVESTASI, FASILITAS TEKNOLOGI, STATUS MAHASISWA DAN GENDER TERHADAP MINAT INVESTASI MAHASISWA UNIVERSITAS PRIMA INDONESIA DI PASAR MODAL - Faathir Nurul Yaasiin; Tina Novianti Sitanggang (JURNAL MUTIARA AKUNTANSI, 2020)
This study aims to determine how much influence investment knowledge, technological facilities, student status and gender have on investment interest. The data used in this study are primary data, the population taken in this study were students of the Faculty of Economics, University of Prima Indonesia, while the research sample taken was accounting students of the Faculty of Economics, Universitas Prima Indonesia who had completed the portfolio theory and investment analysis courses and are currently still registered at the Faculty of Economics, University of Prima Indonesia. The sample in this study was 236 respondents who were taken using the Slovin formula. The data were processed using SPSS assistance. The analytical tool used in this study is multiple linear regression. The results of this study indicate that the variables of investment knowledge, technology facilities and gender have a positive effect on investment interest, while the variable student status has a negative effect on investment interest